2009
DOI: 10.2298/abs0903419t
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Botrytis cinerea isolates from small fruits and grapevine in Serbia

Abstract: Twenty-six single-spore isolates of Botrytis cinerea from blackberry, raspberry, strawberry, and grapevine were investigated using transposable elements, morphological characterization, and sensitivity to fungicides. Both transposable elements, Flipper and Boty, were detected among isolates from all the hosts. Six vacuma (without transposable elements) and seven transposa (containing both elements) isolates were found to be present in sympatry in Serbia. Isolates containing only the Boty element were detected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
(31 reference statements)
1
14
0
2
Order By: Relevance
“…Afterwards, phenotypic observations were performed based on mycelial aspect, sporulation and sclerotia production. The isolates were classified into eight morphological types described by Martinez et al (2003) and used earlier by Tanović et al (2009) (Figure 1). …”
Section: Morphological Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, phenotypic observations were performed based on mycelial aspect, sporulation and sclerotia production. The isolates were classified into eight morphological types described by Martinez et al (2003) and used earlier by Tanović et al (2009) (Figure 1). …”
Section: Morphological Characterizationmentioning
confidence: 99%
“…In addition, the fungus causes significant losses during shipping and marketing, which makes it one of the most important pathogens of raspberry worldwide (Nikolić et al, 2008). B. cinerea (anamorph of Botryotinia fuckeliana), a pathogen that causes grey mould on a wide variety of plants worldwide, has been extensively studied on many major crops, including grapes, strawberry, kiwifruit, tomato and bulb crops, while its characterization on raspberry is still limited and based on a small number of isolates (Tanović et al, 2009). Well-documented phenotypic diversity of the pathogen is usually explained by the multinucleate and heterocaryotic nature of hyphae or conidia and aneuploid state of nuclei (Hansen & Smith, 1932;Büttner et al, 1994;Chardonnet et al, 2000;Yourman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the genetic plasticity of B. cinerea, a high evolutionary potential of resistant strains makes fungicides to be hardly adopted by farmers in order to totally eradicate grey mold disease. The potential of some fungicides had been evaluated on the basis of the phenotypic and genetic diversity among fungal strains (Ahmed and Naim, 1993;Tanovic et al, 2009). However, more evaluations are needed to be studied as these fungicides are always affected by environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the presence/absence of these two transposable elements, many authors confirmed that B. cinerea is a complex species, composed of at least two genetic groups, transposa and vacuma. Transposa group contains both transposable elements, whereas vacuma group has neither of these two elements (Vaczy et al, 2008;Tanovic et al, 2009). Furthermore, isolates that contain only boty (Tanovic et al, 2009) or only flipper (Vaczy et al, 2008;Kuzmanovska et al, 2012) are also detected.…”
Section: Introductionmentioning
confidence: 99%
“…Transposa group contains both transposable elements, whereas vacuma group has neither of these two elements (Vaczy et al, 2008;Tanovic et al, 2009). Furthermore, isolates that contain only boty (Tanovic et al, 2009) or only flipper (Vaczy et al, 2008;Kuzmanovska et al, 2012) are also detected. Control of grey mold disease in tomato is mainly based on common applications of fungicides, but the key problem is the ability of the fungus to become resistant to frequently applied fungicides (Zhao et al, 2010;Esterio et al, 2011;Walker et al, 2013;Hahn, 2014).…”
Section: Introductionmentioning
confidence: 99%